Abstraction and concepts: when, how, where, what and why?. Issue 10 (26th November 2019) - Yee, Eiling
ABSTRACT: It is increasingly apparent that sensorimotor information is a constitutive part of conceptual knowledge. Yet all concepts, even highly concrete ones (e.g. dog ) include information that is abstracted across individual episodes of experience, departing somewhat from direct sensory or motor input. This process of abstraction is the essence of conceptual structure. This Special Issue brings together developmental, experimental, computational and cognitive neuroscientific perspectives on abstraction. The contributions address questions like: When during development do our concepts become less directly tied to sensory or motor knowledge? How (and where) in the brain does the process of abstraction happen? And what is the role of a concept's label in abstraction? In answering these questions, the contributions highlight that context–the developmental contexts of our first episodic experiences, and the linguistic contexts that accompany the development of conceptual knowledge in both children and adults–is at the root of conceptual knowledge.